2023
DOI: 10.1111/jdv.19530
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in patients with generalized pustular psoriasis: A systematic literature review

S. E. Choon,
C. De La Cruz,
P. Wolf
et al.

Abstract: Generalised pustular psoriasis (GPP) is a rare, chronic, neutrophilic inflammatory skin disease characterised by episodes of widespread eruption of sterile, macroscopic pustules that can be accompanied by systemic inflammation and symptoms. A systematic literature review and narrative synthesis were conducted to determine the impact of GPP on patients’ health‐related quality of life (HRQoL) and patient‐reported severity of symptoms, and to compare its impact to patients with plaque psoriasis (plaque PsO). Sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Further data describing the acute and long-term burden of GPP, and the health economic pathways and burden of disease, in various populations have been published recently [ 53 , 57 60 ]. However, there remains an unmet need for improved guidelines for GPP diagnosis and management, improved recognition and understanding of GPP by HCPs, and multi-level support involving primary care, emergency care, and dermatologists [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further data describing the acute and long-term burden of GPP, and the health economic pathways and burden of disease, in various populations have been published recently [ 53 , 57 60 ]. However, there remains an unmet need for improved guidelines for GPP diagnosis and management, improved recognition and understanding of GPP by HCPs, and multi-level support involving primary care, emergency care, and dermatologists [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 The unpredictability of GPP flare presents an obstacle to effective long-term management and leads to considerable clinical, financial and psychological strain for patients. 3,4 Our previous studies and a recent clinical trial showed that flares are highly prevalent among GPP patients, underscoring the significant importance of predicting and preventing GPP flares. 5,6 Therefore, we conducted this study to elucidate the risk factors of GPP flare, and construct a predictive model grounded in the clinical characteristics of patients to forecast the occurrence of GPP flares.…”
Section: Development and Validation Of A Prognostic Model For Predict...mentioning
confidence: 93%
“…A recent systemic literature review identified 20 studies on HRQoL in patients with GPP [ 18 ], of which seven related to patients with GPP and plaques psoriasis and 13 related to patients with GPP only. Most studies addressed dermatological-specific HRQoL, while few addressed general HRQoL.…”
Section: Introductionmentioning
confidence: 99%